Identification and expression analysis of heat shock transcription factors in the wild Chinese grapevine (Vitis pseudoreticulata) - Hu, Yang (Plant physiology and biochemistry : PPB, 2016)
Copyright © 2015 Elsevier Masson SAS. All rights reserved.